Flocculation of algae Chlorella vulgaris using AFlok-BP1 and aluminum sulfate (Alum) - A. B., Fatin Nur Lyana; Omar, Rozita; Harun, M. R.; Wan Ab. Karim Ghani, Wan Azlina; Idris, A. (Penerbit Universiti Malaysia Terengganu, 2016)
Chlorella vulgaris is a marine microalgae with high protein and carbohydrate contents which can be extracted to produce fine chemicals, nutraceutical and pharmaceutical products. Dewatering step is required to extract these compounds. The flocculation technique which generally uses chemical flocculants such as Alum has negative environmental impact and is not suitable for food and pharmaceutical grade products. In this study, bioflocculant (AFlok-BP1) and Alum was used to flocculate C. vulgaris for high biomass concentration production. Autoflocculation of the algae was done by pH adjustment (8-11) utilizing HCl and NaOH. AFlok-BP1 was added to algae culture at pH adjustment between 5 and 8 for to give final concentration of 10-40 mg/L. Meanwhile, Alum was added to the culture at pH between 7 and 10 to give final concentration of 600-840 mg/L. The flocculation efficiency was evaluated using turbidity tests. pH 11 was found to give the highest efficiency in the autoflocculation test. In general, at pH 6 regardless of the AFlok dosage gives high flocculation efficiency around 80%. However, at lower dosage of 10 mg/L at pH 8 gives a comparable efficiency. Increasing AFlok-BP1 dosage above 20 mg/L did not increase the efficiency though resulted bigger flocs, thus reducing the settling time. Conversely, higher amount of Alum was needed to flocculate the algae at 720 and 840 mg/L Alum dosage and at higher pH (pH 10). Lowering the dosage resulted in severely reduced flocculation efficiency especially at lower pH. This study shows that the use of bioflocculant AFlok-BP1 offers high flocculation performance with only minimal usage of toxic chemicals (acid/alkali) thus it is more eco-friendly.